1999
DOI: 10.1021/ic981277r
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and Trinuclear Nickel(II) Complexes with Sulfur-Containing Oxime Ligands:  Uncommon Templated Coupling of Oxime with Nitrile

Abstract: 4,7-Dithiadecane-2,9-dione dioxime forms both violet and purple-black nickel(II) complexes with unexpected structural properties, quite unlike the square-planar chelates formed by its dithiaundecane homologue. Their perchlorate salts were isolated and examined crystallographically. The lilac product [Ni{(Dtox)(CH(3)CNH)(2)}](ClO(4))(2) entails a bis(iminoether) ligand formed by coupling of the dioxime with two moles of acetonitrile. The purple-black complex results from further ligand deprotonation, to yield t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 34 publications
4
31
0
Order By: Relevance
“…The transition w 1 is split into a double-humped peak, which can be interpreted as indicated above, but attempts to calculate the Racah B parameter produced values which were physically unrealistic for those reasons. The values obtained for 10 Dq (10 400 -13 500 cm − 1 ) are reasonable for pseudo-octahedral high-spin Ni(II) complexes with strong in-plane fields [7,40,41]. The values of 10 Dq are larger for those compounds which possess an axial thioether relative to those with ether axial donors.…”
Section: Nickel(ii) Complexesmentioning
confidence: 55%
See 2 more Smart Citations
“…The transition w 1 is split into a double-humped peak, which can be interpreted as indicated above, but attempts to calculate the Racah B parameter produced values which were physically unrealistic for those reasons. The values obtained for 10 Dq (10 400 -13 500 cm − 1 ) are reasonable for pseudo-octahedral high-spin Ni(II) complexes with strong in-plane fields [7,40,41]. The values of 10 Dq are larger for those compounds which possess an axial thioether relative to those with ether axial donors.…”
Section: Nickel(ii) Complexesmentioning
confidence: 55%
“…Acetonitrile for electrochemistry was distilled off P 4 O 10 under N 2 . 3-Chloro-2-propanone oxime and 3-chlorobutanone oxime were prepared according to literature procedures [7,17]. Proton NMR spectra were obtained on a Bruker AM250 spectrometer using CDCl 3 as solvent with TMS as internal standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] [Ni 3 (dtox)-(dtoxH) 2 ](ClO 4 ) 2 (dtoxH 2 = 4,7-dithiadecane-2,9-dione dioxime), [{Ni 3 (medpt) 3 (NCS) 4 }(µ 3 -CO 3 )] [medpt = bis(3-aminopropyl)methylamine], and [{Ni 3 (medpt) 3 (NCSe) 4 }-(µ 3 -CO 3 )] are further examples of irregular triangular nickel(II) complexes, structurally characterized, showing weak and very strong antiferromagnetic interactions, respectively. [10][11][12] We can notice that in all the above-mentioned nickel(II) complexes, except for that containing the Ni-(CN) 4 2-unit, the central atoms are in a deformed octahedral arrangement.…”
Section: Introductionmentioning
confidence: 96%
“…For the aqua pathways, the Ni-O-Ni bond angles are 122.8°, out of the range 80-100° for ferromagnetic coupling. [6][7][8] Hence, the overall ferromagnetic interaction in 1 should be originated from the ferromagnetic contribution (J F ) of carboxylate bridges that is larger than the antiferromagnetic contribution (J AF ) of the aqua bridges. Previous reports 9 have shown that the solely syn-syn carboxylate bridge transmits moderate antiferromagnetic coupling between Ni(II) ions.…”
Section: Resultsmentioning
confidence: 99%